Neuroprotective and tumoricidal activities of cardiac glycosides. Could oleandrin be a new weapon against stroke and glioblastoma? - ALTURFAN, EBRU IŞIK (TAYLOR & FRANCIS LTD, 2018)
Cardiac glycosides induce a strong immunological cancer cell cytotoxicity, in which the released intracellular components of dying tumor cells (e.g. calreticulin, HMGB1 and ATP) stimulate immunity and help in eradicating cancer. Among the cardiac glycosides, oleandrin is an inhibitor of P-glycoprotein expression and exerts excellent penetration through the blood-brain barrier which also harbors neuroprotective and anti-glioma efficacies. Cardiac glycosides also exert neuroprotective activities, one explanation for such an action is the metabolic arrest as a defense strategy against hypoxia. Recently, it was also shown that oleandrin increases survival of glioma-implanted mice alone and in synergy with temozolomide, which also associated with the release of brain derived neurotrophic factor and activation of its receptor TrkB. In conclusion, oleandrin strongly deserves to be studied as a candidate molecule in treatment of neurodegenerative and neurooncological diseases.
Keywords: Cardiac glycoside; oleandrin; anticancer activity; brain tumor; glioblastoma; AMYOTROPHIC-LATERAL-SCLEROSIS; BOVINE ADRENOCORTICAL-CELLS; TRAIL-MEDIATED APOPTOSIS; NERIUM-OLEANDER; ENDOGENOUS DIGITALIS; ISCHEMIC-STROKE; ATPASE ACTIVITY; DIGOXIN; CANCER; BRAIN